Effects of zerumbone on anxiety, learning and memory in scopolamine-induced animal model of dementia - Nasserizad, Sahba Jafarian (2019)
Dementia is a general term to describe decline of mental ability associated with cognitive impairment, losing memory or other thinking skills that interfere with occupational functioning and usual social activities. The most common type of dementia is Alzheimer’s disease (AD) which is a neurodegenerative disease related to cognitive and behavioural impairments. The major AD drugs are known as acetylcholinesterase inhibitors (AChEI) which are not acceptable in a wide range of patients due to resistance, adverse effect, and poor efficacy. Based on recent studies, herbal medicine such as zerumbone (2,6,9,9-tetramethyl-[2E,6E,10E]-cycloundeca- 2,6,10-trien-1-one) which is a sesquiterpenoid compound, could be a new source for inhibition of AChE enzyme. Zerumbone was first isolated from the rhizomes oil of Zingiber zerumbet Smith, in 1956. It has the potential for treatment of cancers, leukemia and virus infection. In this study, scopolamine which is a muscarinic antagonist drug was used to induce some dementia-like behaviours in rats and the effect of zerumbone (1 and 10mg/kg) was investigated through some behavioural and biochemical experiments. All the results were expressed as mean ± standard error of mean (SEM) and analyzed using one-way analysis of variance (ANOVA) followed by Tukey's post hoc analysis. p<0.05 was considered statistically significant. Behavioural assessments such as open field tests, elevated plus maze, and Morris water maze were performed to assess general locomotors activity, anxiety-like behaviours, and learning and memory processes respectively, in Sprague-Dawley rats pre-treated with scopolamine. Based on the results obtained, zerumbone 1 mg/kg significantly reduced total activity, stereotype, and total distance travelled in the open field arena. Moreover, zerumbone 1 and 10mg/kg, respectively showed high percent of time spent in open arms; and increased number and percent of entry to open arms, in the elevated plus maze. Also, in the Morris water maze, zerumbone 1 and 10mg/kg showed learning improvement by significant reduction in mean escape latency time. Interestingly, single administration of zerumbone (1 and 10mg/kg) reversed the hyperactivity, anxiety-like behaviour, and learning impairment effects of scopolamine to normal condition. Biochemical experiments have been done on the brain samples which were sectioned to three parts (prefrontal cortex, hippocampus, and cortex) and prepared for acetyl cholinesterase (ACHE) enzyme activity and choline acetyltransferase (ChAT) protein expression. AChE enzyme activity is significantly reduced by zerumbone 1mg/kg in the hippocampus brain samples compared to all groups. On the other hand, lower dose of zerumbone reversed the effect of scopolamine by decreasing AChE enzyme activity. Western blotting was also used to determine ChAT protein expression among all groups and it was concluded that there isn’t any significant differences between all groups and both dosage of zerumbone were not effective towards ChAT protein expression. In conclusion, zerumbone showed improvement in learning process while reduced hyperactivity, anxiety/depression, and AChE enzyme activity in scopolamine pre-treated rats. Thus, zerumbone could be a great candidate for treatment of dementialike behaviour. Although, more research need to be done to find out its mechanism of action.